Preliminary Analysis of the Formation Mechanism of Floret Color in Broccoli (Brassica oleracea L var. italica) Based on Transcriptomics and Targeted Metabolomics - Qingqing Shao; Mindong Chen; Saichuan Cheng; Huangfang Lin; Biying Lin; Honghui Lin; Jianting Liu; Haisheng Zhu (Plants)
Floret color is a crucial phenotypic trait in broccoli, serving as an indicator of maturity and determining its market value. However, the mechanisms underlying color variation remain unclear. In this study, six broccoli varieties with different floret colors at harvest were chosen as materials. The color difference and pigment content of florets were measured, and a combined analysis of anthocyanin-targeted metabolome and transcriptome was conducted. Our findings revealed that chlorophyll a primarily influences green, yellow-green, and light green coloration, while the wax content may contribute to gray-green coloration. The blue-green and dark blue-green coloration are regulated by both chlorophyll a and anthocyanins. Targeted metabolomics identified five anthocyanin compounds, with peonidin-3-O-glucoside as a key metabolite for blue-green coloration and delphinidin-3-O-glucoside-5-O-galactoside and peonidin-3,5-O-diglucoside for dark blue-green coloration. Transcriptomic analysis identified CHLG as a potential key regulator for yellow-green and light-green floret coloration. The blue-green coloration appears to be coregulated by a combination of genes, including the chlorophyll biosynthesis gene HEMF; anthocyanin biosynthesis genes (PAL, FLS, and UGT); and chlorophyll degradation genes (SGR, PPD, and NYC). Furthermore, upstream genes involved in both chlorophyll metabolism (CHLI, CHLD, CHLM, DVR, and CLH) and anthocyanin biosynthesis (PAL, 4CL, CHS, F3′H, and FLS) play crucial roles in determining the dark blue-green coloration of florets. Meanwhile, transcription factors of the WRKY, NAC, and TCP families are involved in chlorophyll metabolism, while those of the bHLH and MYB families participate in anthocyanin synthesis. The WGCNA identified one Hub gene for chlorophyll metabolism and two for anthocyanin synthesis. In conclusion, 35 candidate genes were identified, including 21 involved in chlorophyll metabolism and 14 in anthocyanin biosynthesis. This study provides novel insights into the molecular mechanisms of floret coloration and establishes a foundation for molecular breeding in broccoli.